Pengaruh Edukasi Dengan Media Booklet Terhadap Kemampuan Kognitif Ibu Dalam Pemberian Makanan Pada Anak Usia Toddler diwilayah Kerja Puskesmas Wori - Olga Hairun; Sri Wahyuni; Nelfa Fitria Takahepis (STIKES Columbia Asia Medan, 2023)
Toddler problems are prone to nutritional health problems, at that time is an important period in the process of toddler growth and development. If the required intake does not meet then toddlers will have less nutritional status. The purpose of this study was to determine the efficacy of booklet media education with maternal cognitive abilities in feeding toddlers. The study was conducted using pre-experimental research method design (one-group pretest-posttest) The sample in this study as many as 15 subjekts were taken using purposive sampling in s research instrument using SAP, leaflets and questionnaires. Furthermore, the collected data was processed using the SPSS program computer version 16.0 to be analyzed with Mc. Nemar's nonparametric test with a meaning level (α) of 0.05. The results of this study show that there is an influence of education with booklet media on the cognitive ability of mothers in feeding todler-aged children in the working area of the wori health center in Manado City. with the value of p = 0.016 it can be said that Ha is accepted and H0 is rejected and it is concluded that Ha has an educational influence with booklet media on the cognitive ability of mothers in food production in toddler-aged children in the work area of the wori health center. The conclusion in this study is the influence of education with booklet media on the cognitive ability of mothers in food production in toddler-aged children in the work area of the wori health center. Suggestions are expected to add useful insight and knowledge about booklet media education on cognitive abilities